Updates in Endoscopic Retrograde Cholangiopancreatography - Gobishangar, S.; Thayalan Dias, S.; Rajendra, S.; Sarma, S.T. (Jaffna Medical Journal, 2024)
Endoscopic retrograde cholangiopancreatography (ERCP) is a specialised endoscopic procedure for managing pancreatic and biliary diseases. Earlier in the 1970s, ERCP was mainly used for diagnostic purposes to evaluate the biliary and pancreatic ducts and surrounding structures. But nowadays, as noninvasive imaging studies advance, it is primarily used for therapeutic purposes though it is used for therapeutic and diagnostic purposes. Therapeutic ERCP is broadly used in conditions that lead to impairment in bile flow and leak. The requirement of the ERCP extended further for evaluation of pancreatitis of unknown aetiology, preoperative evaluation of the patient with chronic pancreatitis and evaluation of the sphincter of Oddi by manometry. Patients should be selected with a clear-cut indication for ERCP, avoiding unnecessary or marginally indicated ERCP, especially in high-risk patients. ERCP is usually performed using a dedicated side-viewing endoscope with the patient positioned prone on a fluoroscopy table under sedation or general anaesthesia. Proper positioning of the duodenoscope is the key to cannulation of the pancreatic or common bile ducts.
Keywords: ERCP; Bile duct stones; Cholangitis; Duodenoscope; Chronic pancreatitis; Minimally invasive therapeutic procedure